Molecular and Genomic Insights of mcr-1-Producing Escherichia coli Isolates from Piglets - Jonathan Rodríguez-Santiago; Nadia Rodríguez-Medina; Elsa María Tamayo-Legorreta; Jesús Silva-Sánchez; Juan Téllez-Sosa; Josefina Duran-Bedolla; Alejandro Aguilar-Vera; Alba Neri Lecona-Valera; Ulises Garza-Ramos; Celia Alpuche-Aranda (MDPI AG, 2022)
The use of colistin in food-producing animals favors the emergence and spread of colistin-resistant strains. Here, we investigated the occurrence and molecular mechanisms of colistin resistance among E. coli isolates from a Mexican piglet farm. A collection of 175 cephalosporin-resistant colonies from swine fecal samples were recovered. The colistin resistance phenotype was identified by rapid polymyxin test and the mcr-type genes were screened by PCR. We assessed the colistin-resistant strains by antimicrobial susceptibility test, pulse-field gel electrophoresis, plasmid profile, and mating experiments. Whole-Genome Sequencing data was used to explore the resistome, virulome, and mobilome of colistin-resistant strains. A total of four colistin-resistant E. coli were identified from the cefotaxime-resistant colonies. All harbored the plasmid-borne mcr-1 gene, which was located on conjugative 170-kb IncHI-2 plasmid co-carrying ESBLs genes. Thus, high antimicrobial resistance rates were observed for several antibiotic families. In the RC2-007 strain, the mcr-1 gene was located as part of a prophage carried on non-conjugative 100-kb-plasmid, which upon being transformed into K. variicola strain increased the polymyxin resistance 2-fold. The genomic analysis showed a broad resistome and virulome. Our findings suggest that colistin resistance followed independent acquisition pathways as clonal and non-genetically related mcr-1-harboring strains were identified. These E. coli isolates represent a reservoir of antibiotic resistance and virulence genes in animals for human consumption which could be potentially propagated into other interfaces.